Alleviation of transient torsional torque stresses of turbine generator shaft segments using CBVLC supplementary controller. (2016) - Kumar, Narendra; Kumar, Sanjiv
In this paper a bus voltage and line current (BVLC) supplementary subsynchronous damping controller (SSDC) is proposed to alleviate subsynchronous resonance (SSR) and damping power system oscillations in a power system. Both eigenvalue investigation and time-domain simulation results verify that the proposed method can damp torsional oscillations of the power system with SVS bus voltage and line current (BVLC) supplementary controller. The results demonstrate that the proposed controller has a successful performance in minimising the SSR. It is shown that the controller is able to stabilise all unstable modes. The study is performed on the system adapted from the IEEE first benchmark model. All the simulations are carried out in MATLAB/Simulink environment.